The Influence of Career Development and Work Environment Toward Job Satisfaction of Office Staff (A Case Study at PT Harrison And Gil Java Semarang) - Fadhilah, Fildzah -; Poerbo, Suryadi -; Suratno, Agus - (Admisi dan Bisnis, 2020)
The purposes of this research were to analyze the influence of career development (X1) and work environment(X2) as independent variables on job satisfaction (Y) as dependent variable at PT. Harrison and Gil Java Semarang. The methods of data collection used questionnaires, literature study and interview. The technique of analysis used in this research was multiple linear regression analysis. The sample of this research are 51 respondents and analytical method used are the validity test, reliability test, classical assumption test, multiple linear regression, coefficient determination, t test and F test. The result of multiple linear regression analysis could be shown by the regression equation Y = 17.124 + 0.318 X1 + 0.201 X2. The coefficient determination of this research was 15.9%, which meant that the contribution of career development and work environment to job satisfaction is 15.9% and the remaining 84.1% is influenced by other variables which are not examined in this research. The result of  this  research  shows  that  career development  and  work environment had positive and significant influence on job satisfaction.